Stigma and health-related quality of life (HRQoL) among people with multidrug-resistant tuberculosis (MDR-TB): A cross-sectional study in Indonesia - Arifin, Bustanul; Sarwadan, Muhamad G.; Wahyudin, Elly; Sarifah, Latifah M.; Fuady, Ahmad; Purba, Fredrick D.; Alkaff, Sylmina D.; Ardiansyah, Akhmad; Madolangan, Jamaluddin (Narra Sains Indonesia, 2025)
Stigma often accompanies people with multidrug-resistant tuberculosis (MDR-TB) and potentially affects their health-related quality of life (HRQoL). The aim of this study was to investigate the stigma faced by patients with MDR-TB, both from the patients' and community's perspective, and its relationship with HRQoL. Data was gathered at the provincial hospital in Makassar, South Sulawesi, Indonesia. The instrument employed in this research was the Indonesian version of the tuberculosis (TB) stigma instrument to assess MDR-TB stigma from the patient and community perspectives. The patient perspective represents how individuals with TB perceive and experience stigma, including the fear of disclosure, isolation, and guilt (feeling responsible for the burden on their family or their own risky behaviors). Meanwhile, the community perspective reflects how individuals with TB perceive societal attitudes towards them, such as social distancing, avoidance, and reluctance to interact. HRQoL was measured using the European quality of life-5 dimensions-5 level version (EQ-5D-5L) instrument. Notably, the evaluation of anxiety and depression is centered on the fifth dimension of the EQ-5D-5L instrument. A total of 210 patients with MDR-TB were included in the study, all of whom reported experiencing stigma. Most participants perceived stigma at a moderate level, with 76% from the patient perspective and 71% from the community perspective. The average EQ-5D-5L index score was 0.72 (95% confidence interval (95%CI): 0.68–0.76). Measurements from both perspectives show similar scores. There is a substantial negative association between the level of stigma and HRQoL, both from the patient's perspective (R2=-0.33; F=102.52; p<0.001) and the community's (R2=-0.32; F=96.76; p<0.001). The study highlights that the stigma of MDR-TB significantly affects the HRQoL from the patient and community perspective.